Canalicular adenoma: A systematic review (2017)
Objective Canalicular adenoma (CA) is an uncommon but unique benign tumor of salivary gland origin. It is the third most common benign tumor of minor salivary glands, representing less than 1% of all salivary neoplasms. A systematic review is presented of reported cases of CA, to determine trends in presentation, diagnostic features, treatment, and patient outcome. Methods Searches of specific databases, as reported, were carried out to identify papers reporting CA. The variables were patient symptoms, tumor location, histopathological findings, demographics, treatment, follow-up, and recurrence. Results 430 cases were identified; the most common location was in the upper lip (66.3%), followed by hard palate (14.5%). The most common clinical presentation was a nodule (46.5%), followed by asymptomatic (29.5%), and discomfort (28.7%). CA was most frequently seen in females (64%). The average age was 66.3 years. 97% of cases were treated surgically. The average follow-up was 136.3 months, and recurrence was reported in 3% of the cases. Conclusion CA shows a strong predilection for the upper lip. CAs are frequently asymptomatic, but the principal symptom was pressure. © 2017 European Association for Cranio-Maxillo-Facial Surgery